The effectiveness of the contents of print advertisements in inducing recall - Tan, Su Wei (2001)
The effectiveness of advertising has became an undeniable truth in assisting advertisers to promote their brand especially through TV advertising. However, the increasing challenges faced by TV advertising like advertisement clustering, zapping and etc. have made the advertisers seeking for alternatives like spreading their advertising budget over other media. The most popular advertising media after TV would be print advertising. Therefore, a better understanding of how consumers interpret print advertisement would help the advertisers to achieve their objectives. The purpose of this research is to determine if there is any significant relationship between the advertisement contents and the attention gained, then the relationship between the attention-gaining advertisement contents and recall of those contents. in addition, the study considers if personal influences like social-demographic factors have any bearing on recall. There were 148 respondents residing in Klang Valler participated in the survey of using a self-administrated questionnaire. The questionnaire measured the attention-gaining factors, recall and contained social-demographic questions. The majority of the respondents were single, Chinese females aged between 21-35 years. most of them possessed at least a Bachelor Degree and worked as professional/management level. They earned a monthly income between RM 1,501-RM 3,000. The findings of multiple linear regression showed that there is a significant relationship between the advertisement contents (executional factors) and attention. Besides, One-Way ANOVA validated the results. The linear regression analysis revealed that there was no significant relationship between the attention gained from the executional style and the recall of those factors. In other words, those executional factors that had attracted the consumers' attention may not be recalled later. The result from Chi-square test showed that there was no relationship between recall and the respondents' social-domgraphic factors such as gender, age, education, race, personal income, marital status and occupation.